APLIKASI PENGELOMPOKAN DATA (CLUSTERING OF DATA) DALAM MEMUDAHKAN MONITORING KETERSEDIAAN BAHAN BAKU OBAT - Suwarningsih, Wiwin (LIPI Press, 2012)
Periodic monitoring of drug raw materials in order to search for expired materials is still done manually. Thus the process of searching for these raw materials is usually slow, since data are store using number based application. Therefore this paper will be discussed how the data for drug raw materials are managed using clustering data mining methods. Drug raw data are stored using clustering so that the searching process will be easier andthe searching time is faster. The result of this research will allow user application to monitor and search for raw materials more easily.